Silicon-carbon composite material as well as preparation method and application thereof

The silicon-carbon composite material with a sulfur-modified porous carbon structure addresses conductivity and volume expansion issues, enhancing battery performance through improved ion and electron conductivity and structural stability, resulting in high-capacity and stable lithium-ion batteries.

CN119170765APending Publication Date: 2024-12-20CHINA FAW CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411229806.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing silicon-carbon composite materials for lithium-ion batteries suffer from fast capacity decay and unsatisfactory cycle performance due to low ion and electron conductivity, volume expansion, and poor structural stability.

Method used

A silicon-carbon composite material with a sulfur-modified porous carbon structure and SC bonds is developed, featuring a three-dimensional ion-conducting and electron-conducting path, enhanced by sulfur-doped carbon frameworks that form defects and increase mechanical strength, promoting Li diffusion and reaction kinetics.

Benefits of technology

The composite material achieves stable long-cycle performance with high capacity retention and improved reaction kinetics, resulting in batteries with excellent high initial efficiency, capacity, and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005025756260000151
    Figure BDA0005025756260000151
  • Figure BDA0005025756260000161
    Figure BDA0005025756260000161
  • Figure BDA0005025756260000171
    Figure BDA0005025756260000171
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a silicon-carbon composite material and a preparation method and application thereof. The silicon-carbon composite material comprises a silicon nanosheet and a composite carbon structure located on the surface of the silicon nanosheet, the composite carbon structure comprises a carbon framework and an element S, and the carbon framework and the element S form an S-C bond. The silicon-carbon composite material has excellent structural stability, the ion and electron conductivity of the silicon negative electrode can be improved, and a three-dimensional ion and electron conduction path is formed in the silicon negative electrode, so that the problem of capacity fading of the pure silicon negative electrode in the circulation process is relieved, the stable long circulation performance is realized, and the high capacity retention rate is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] As energy storage systems in applications such as electric vehicles and portable electronic devices, lithium-ion batteries need to meet the requirements of large capacity, long cycle life, and good safety performance. However, there are some difficult-to-solve problems with traditional lithium-ion battery negative electrode materials, including low theoretical specific capacity of carbon-based materials, volume expansion of silicon-based materials, low initial efficiency, and poor conductivity.

[0003] In the current carbon-based negative electrode production route, most material manufacturers on the market compound artificial graphite through uniform coating, structural design and other production processes. However, the theoretical specific capacity of graphite materials of 372mAh / g obviously limits its application in the next generation of lithium-ion batteries. Negative electrode materials are crucial to the cycle life and capacity of batteries. Silicon is abundant in the earth's crust and has a wide range of sources. It is the negative electrode material with the highest theoretical specific capacity (4200mAh / g), and compared with lithium metal, it is not easy to form lithium dendrites, playing an important role in improving battery energy density and safety.

[0004] However, current silicon-carbon composite materials still have problems such as fast capacity decay rate and unsatisfactory cycle performance.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One object of the present invention is to provide a silicon-carbon composite material to solve the technical problems of fast capacity decay rate and unsatisfactory cycle performance of the silicon-carbon composite materials in the prior art. The silicon-carbon composite material of the present invention has excellent structural stability, can improve the ion and electron conductivity of the silicon negative electrode, and form a three-dimensional ion-conducting and electron-conducting path inside the silicon negative electrode, thereby alleviating the capacity decay problem of the pure silicon negative electrode during the cycle, so as to achieve stable long-cycle performance and obtain a high capacity retention rate.

[0007] Another object of the present invention is to provide a method for preparing the silicon-carbon composite material. The method is simple and easy to implement, and a silicon-carbon composite material with high capacity and stable structure can be obtained through the coordination of various steps.

[0008] Another object of the present invention is to provide a negative electrode sheet.

[0009] Another object of the present invention is to provide a battery.

[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0011] A silicon-carbon composite material comprises a silicon nanosheet and a composite carbon structure located on the surface of the silicon nanosheet, wherein the composite carbon structure comprises a carbon framework and element S, and the carbon framework and the element S form an SC bond.

[0012] In some embodiments, the composite carbon structure comprises C-SO x -C and HS x -C.

[0013] In some embodiments, the ratio of the mass of the composite carbon structure to the mass of the silicon-carbon composite material is 0.7 to 0.9.

[0014] In some embodiments, the mass ratio of the element S to the carbon framework is 1:(1-4).

[0015] In some embodiments, the silicon nanosheet has a thickness of 5 to 10 nm.

[0016] In some embodiments, the first coulombic efficiency of a battery prepared from the silicon-carbon composite material is greater than 81%.

[0017] In some embodiments, the capacity retention rate of a battery prepared from the silicon-carbon composite material after 250 cycles is greater than 71%.

[0018] The method for preparing the silicon-carbon composite material comprises the following steps:

[0019] The carbon source, amorphous sulfur, silicon nanosheets and an organic solvent are mixed to obtain a mixed slurry, and the mixed slurry is heated and carbonized.

[0020] In some embodiments, the mass ratio of the silicon nanosheets, the carbon source, and the amorphous sulfur is 2:(0.7-1):(0.6-0.8).

[0021] In some embodiments, the mass ratio of the total mass of the silicon nanosheets, the carbon source, and the amorphous sulfur to the organic solvent is (170-200) mg: (1.8-3) mL.

[0022] In some embodiments, the carbon source comprises at least one of a resin and a pitch.

[0023] In some embodiments, the silicon nanosheet has a thickness of 5 to 10 nm.

[0024] In some embodiments, the method for preparing the silicon nanosheets specifically includes: washing the calcium disilicide with an alkaline solution and then chemically stripping it with concentrated hydrochloric acid; or, heat-treating silicon tetrachloride liquid to obtain silicon atoms in a hydrogen atmosphere and depositing them on the surface of the heated silicon dioxide.

[0025] In some embodiments, the mixing treatment includes ultrasonic treatment and stirring treatment.

[0026] In some embodiments, the temperature of the heating treatment is 75-85°C.

[0027] In some embodiments, the carbonization treatment includes a first carbonization and a second carbonization; the temperature of the first carbonization is 350-450°C, and the time of the first carbonization is 5-7 hours; the temperature of the second carbonization is 750-850°C, and the time of the second carbonization is 2-4 hours.

[0028] In some embodiments, the carbonization treatment is performed under protective gas conditions.

[0029] A negative electrode sheet comprises the silicon-carbon composite material.

[0030] A battery comprises the negative electrode sheet.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] (1) The silicon-carbon composite material of the present invention has a sulfur-modified porous carbon structure which can improve the ionic and electronic conductivity of the silicon negative electrode and form a three-dimensional ion-conducting and electron-conducting path inside the silicon negative electrode, thereby alleviating the capacity attenuation problem of the pure silicon negative electrode during the cycle, so as to achieve stable long-cycle performance and obtain a high capacity retention rate; the sulfur-doped carbon framework contains sulfur functional groups which can form SC bonds and increase the cross-linking of the carbon layer, thereby increasing the mechanical strength of the carbon matrix to adapt to the change in Si volume and maintain the integrity of the matrix under stress; the larger sulfur-containing functional groups will distort the carbon layer structure, form defects, and increase the interlayer spacing, thereby providing more diffusion paths, reducing the surface activation energy, and improving the reaction kinetics of lithium ions. The larger carbon layer spacing and defects caused by sulfur doping can promote Li diffusion and electrode reaction.

[0033] (2) The preparation method of the silicon-carbon composite material of the present invention, the carbon source contains defective rigid polycyclic aromatic hydrocarbons. During the process of converting the carbon source into a carbonaceous material, sulfur reacts with the defects in the polycyclic aromatic hydrocarbons to form sulfur-containing functional groups between different carbon layers, and the excess sulfur is converted into gas and forms a porous structure. The larger carbon layer spacing and defects generated by sulfur doping can promote Li diffusion and electrode reaction; the two-dimensional silicon nanosheets can effectively alleviate the problem of volume expansion, and the higher specific surface area provides a large number of active sites for the reaction of lithium ions. After carbonization treatment, the sulfur functional groups remaining between different carbon layers can form SC bonds to increase the cross-linking of the carbon layers, thereby increasing the mechanical strength of the carbon matrix to adapt to the change in Si volume, maintain the integrity of the matrix under stress, and improve the reaction kinetics of lithium ions.

[0034] (3) The battery of the present invention has excellent high initial efficiency, high capacity, good cycle stability and good safety. DETAILED DESCRIPTION

[0035] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0036] According to one aspect of the present invention, the present invention relates to a silicon-carbon composite material, comprising a silicon nanosheet and a composite carbon structure located on the surface of the silicon nanosheet, wherein the composite carbon structure comprises a carbon framework and element S, and the carbon framework and the element S form an SC bond.

[0037] The silicon-carbon composite material of the present invention has a core layer of silicon nanosheets and a coating layer of a composite carbon structure. In the composite carbon structure, the carbon framework has a porous structure. The sulfur-modified porous carbon structure can improve the ionic and electronic conductivity of the silicon negative electrode, and form a three-dimensional ion-conducting and electron-conducting path inside the silicon negative electrode, thereby alleviating the capacity decay problem of the pure silicon negative electrode during the cycle process, so as to achieve stable long-cycle performance and obtain a high capacity retention rate; the sulfur-doped carbon framework contains sulfur functional groups that can form SC bonds, increase carbon layer cross-linking, thereby increasing the mechanical strength of the carbon matrix to adapt to changes in Si volume and maintain the integrity of the matrix under stress; in addition, the larger sulfur-containing functional groups will distort the carbon layer structure, form defects, increase the interlayer spacing, thereby providing more diffusion paths, reducing surface activation energy, and improving the reaction kinetics of lithium ions. The larger carbon layer spacing and defects generated by sulfur doping can promote Li diffusion and electrode reaction.

[0038] In some embodiments, the composite carbon structure comprises C-SO x -C and HS x -C, such as C-SO-C and HS 0.5 -C.

[0039] In some embodiments, the ratio of the mass of the composite carbon structure to the mass of the silicon-carbon composite material is 0.7 to 0.9. The ratio of the mass of the composite carbon structure to the mass of the silicon-carbon composite material includes but is not limited to 0.7, 0.72, 0.75, 0.78, 0.8, 0.82, 0.85, 0.88 or 0.9, or any range between the two. In some embodiments, the mass ratio of the element S to the carbon framework is 1:(1 to 4), including but not limited to 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, or any range between the two. The ratio of the mass of the composite carbon structure to the mass of the silicon-carbon composite material and the mass ratio of the element S to the carbon framework in the present invention are within the above range, which can make the silicon-carbon composite material have more excellent electrochemical properties, and the structural damage caused by the volume expansion / contraction during the de- / insertion of lithium by the silicon negative electrode is greatly alleviated by the porous carbon structure modified by sulfur, which can ensure the necessary ion-electron transport network inside the silicon negative electrode and the structural stability of the electrode during the cycle, so that the battery has the characteristics of high capacity and high cycle stability. If the ratio of the mass of the composite carbon structure to the mass of the silicon-carbon composite material is too high or too low, the capacity of the battery is reduced and the stability is deteriorated.

[0040] In some embodiments, the thickness of the silicon nanosheet is 5-10 nm, including but not limited to 5 nm, 6 nm, 7 nm, 8 nm, 10 nm, etc., or any range between the two.

[0041] In some embodiments, the first coulombic efficiency of the battery prepared from the silicon-carbon composite material is greater than 81%, including but not limited to 81%, 81.5%, 85%, 88%, 90%, 92%, etc., or any range between the two. The battery obtained from the silicon-carbon negative electrode material of the present invention has excellent first coulombic efficiency.

[0042] In some embodiments, the capacity retention rate of the battery prepared from the silicon-carbon composite material after 250 cycles is greater than 71%, including but not limited to 71%, 75%, 78%, 80%, 82%, 85%, 88%, 90%, etc., or any range value between the two. The silicon-carbon composite material of the present invention has excellent cycle stability.

[0043] According to another aspect of the present invention, the present invention also relates to a method for preparing the silicon-carbon composite material as described above, comprising the following steps:

[0044] The carbon source, amorphous sulfur, silicon nanosheets and an organic solvent are mixed to obtain a mixed slurry, and the mixed slurry is heated and carbonized.

[0045] In the preparation method of the silicon-carbon composite material of the present invention, since the carbon source contains defective rigid polycyclic aromatic hydrocarbons, in the process of converting the carbon source into a carbonaceous material, sulfur reacts with defects in the polycyclic aromatic hydrocarbons to form sulfur-containing functional groups between different carbon layers, and the excess sulfur is converted into gas and forms a porous structure. The larger carbon layer spacing and defects generated by sulfur doping can promote Li diffusion and electrode reaction; the two-dimensional silicon nanosheet itself is a layered structure that can effectively alleviate the problem of volume expansion, and the higher specific surface area provides a large number of active sites for the reaction of lithium ions, so that this material has more outstanding reaction kinetics. The materials are mixed to form a uniform mixed slurry, which is further heat treated to remove the solvent. After the carbonization treatment, the sulfur functional groups remaining between different carbon layers can form SC bonds to increase the cross-linking of the carbon layers, thereby increasing the mechanical strength of the carbon matrix to adapt to the change in Si volume, maintain the integrity of the matrix under stress, and improve the reaction kinetics of lithium ions.

[0046] In some embodiments, the mass ratio of silicon nanosheets, carbon source and amorphous sulfur is 2: (0.7-1): (0.6-0.8). In some embodiments, the mass ratio of silicon nanosheets, carbon source and amorphous sulfur includes but is not limited to 2: 0.7: 0.6, 2: 0.8: 0.8, 2: 0.9: 0.6, 2: 1: 0.6, 2: 1: 0.7, 2: 1: 0.8, etc. The silicon nanosheets, carbon source and amorphous sulfur of the present invention adopt a suitable mass ratio, thereby ensuring that the obtained carbon layer is better cross-linked, ensuring the mechanical strength of the composite carbon structure to adapt to the change in Si volume; at the same time, it can ensure that the larger sulfur-containing functional groups will distort the carbon layer structure, form defects, increase the interlayer spacing, thereby providing more diffusion paths, reducing the surface activation energy, and improving the reaction kinetics of lithium ions.

[0047] In some embodiments, the mass ratio of the total mass of silicon nanosheets, carbon source and amorphous sulfur to the organic solvent is (170-200) mg: (1.8-3) mL.

[0048] In some embodiments, the carbon source comprises at least one of a resin and a pitch. The resin comprises a phenolic resin, (C6H6O·CH2) x .

[0049] In some embodiments, the thickness of the silicon nanosheet is 5 to 10 nm. In some embodiments, the thickness of the silicon nanosheet includes but is not limited to 5 nm, 5.5 nm, 6 nm, 7 nm, 8 nm, 9 nm or 10 nm, or any range between the two. The silicon nanosheet of the present invention has a suitable thickness to ensure that the obtained silicon-carbon composite material has better electrochemical performance.

[0050] In some embodiments, the method for preparing silicon nanosheets specifically includes: washing calcium disilicide with an alkali solution, and then chemically exfoliating with concentrated hydrochloric acid. The alkali solution includes a sodium hydroxide solution. The concentration of the concentrated hydrochloric acid is 10 to 14 mol / L.

[0051] In some embodiments, the method for preparing silicon nanosheets specifically includes: heat-treating silicon tetrachloride liquid to obtain silicon atoms and deposit them on the surface of heated silicon dioxide in a hydrogen atmosphere. The heat treatment temperature is 55-75°C.

[0052] The two-dimensional silicon nanosheets obtained by the above-mentioned preparation method of silicon nanosheets of the present invention have a layered structure that can effectively alleviate the problem of volume expansion. At the same time, the high specific surface area can provide a large number of active sites for the reaction of lithium ions, thereby making this material have more excellent reaction kinetics.

[0053] In some embodiments, the mixing process includes ultrasonic treatment and stirring treatment. The materials are fully mixed by ultrasonic treatment and stirring treatment.

[0054] In some embodiments, the temperature of the heating treatment is 75-85° C., including but not limited to 75° C., 80° C., 82° C., 85° C., etc., or any range between the two. The organic solvent is removed by a suitable heating treatment temperature.

[0055] In some embodiments, the carbonization treatment includes a first carbonization and a second carbonization; the temperature of the first carbonization is 350-450°C, including but not limited to 350°C, 380°C, 400°C, 450°C, etc., or any range between the two; the time of the first carbonization is 5-7h, including but not limited to 5h, 5.5h, 6h, 6.5h or 7h, etc., or any range between the two. The temperature of the second carbonization is 750-850°C, including but not limited to 750°C, 780°C, 800°C, 820°C or 850°C, etc., or any range between the two; the time of the second carbonization is 2-4h, including but not limited to 2h, 2.5h, 3h, 3.5h or 4h, etc., or any range between the two. In some embodiments, the carbonization treatment is carried out under protective gas conditions, such as argon, helium, etc. The present invention can control the amount of sulfur-containing functional groups through suitable carbonization treatment conditions to ensure the structural stability of the final silicon-carbon composite material so that it has a higher capacity.

[0056] In a preferred embodiment, the method for preparing the silicon-carbon composite material comprises the following steps:

[0057] (a) Preparation of silicon nanosheets: Calcium disilicide is rinsed with an alkaline solution and then chemically stripped with 10-14 mol / L concentrated hydrochloric acid; alternatively, silicon tetrachloride liquid is heat treated at 55-75°C to obtain silicon atoms in a hydrogen atmosphere and deposit them on the surface of the heated silicon dioxide; silicon nanosheets with a thickness of 5-10 nm are obtained.

[0058] (b) subjecting a mixed system of the carbon source, amorphous sulfur, the silicon nanosheets obtained in step (a) and an organic solvent to ultrasonic treatment and stirring to obtain a mixed slurry.

[0059] (c) heating the mixed slurry at a temperature of 75 to 85° C. and then carbonizing the mixed slurry under protective gas conditions, the carbonization treatment comprising a first carbonization and a second carbonization; the first carbonization temperature is 350 to 450° C., the first carbonization time is 5 to 7 hours; the second carbonization temperature is 750 to 850° C., the second carbonization time is 2 to 4 hours.

[0060] According to another aspect of the present invention, the present invention also relates to a negative electrode sheet comprising the silicon-carbon composite material.

[0061] The negative electrode sheet of the present invention comprises a negative electrode current collector and a negative electrode layer located on at least one side of the negative electrode current collector, wherein the negative electrode layer comprises the silicon-carbon composite material, a conductive agent and a binder. The conductive agent comprises conductive carbon black (Super P). The binder comprises styrene-butadiene rubber (SBR). The negative electrode current collector comprises copper foil.

[0062] In one embodiment, the preparation method of the negative electrode sheet comprises: mixing the above silicon-carbon composite material, the conductive agent and the binder to form a negative electrode slurry, applying the negative electrode slurry to the surface of the negative electrode current collector by drop coating or blade coating to obtain a negative electrode slurry with a loading of 0.15 to 0.3 mg / cm 2 The negative electrode sheet. The loading includes but is not limited to 0.15 mg / cm 2 , 0.18mg / cm 2 , 0.2mg / cm 2 , 0.25mg / cm 2 or 0.3mg / cm 2 wait.

[0063] According to another aspect of the present invention, the present invention also relates to a battery comprising the negative electrode sheet.

[0064] The battery of the present invention comprises a negative electrode sheet, a positive electrode sheet, a separator and an electrolyte.

[0065] The battery of the present invention has excellent structural stability, high capacity, high initial efficiency and good cycle stability.

[0066] The following is further explained in conjunction with specific embodiments and comparative examples.

[0067] Example 1

[0068] A method for preparing a silicon-carbon composite material comprises the following steps:

[0069] (1) Commercial calcium disilicide was rinsed with sodium hydroxide and then chemically exfoliated with 12 mol / L concentrated hydrochloric acid to obtain a two-dimensional silicon nanosheet with a thickness of 8 nm.

[0070] (2) According to the mass ratio of two-dimensional silicon nanosheets: resin: amorphous sulfur = 2:1:0.6, 112 mg of silicon nanosheets, 56 mg of resin and 33.6 mg of amorphous sulfur were weighed and added into 2 mL of DMF, and a uniformly mixed slurry was obtained by ultrasonic treatment and stirring. The resin was phenolic resin.

[0071] (3) The mixed slurry was heated to 80°C to remove DMF, and then the obtained sample was carbonized at 400°C for 6 h and at 800°C in an Ar atmosphere for 3 h.

[0072] The method for preparing a negative electrode sheet comprises the following steps:

[0073] The silicon-carbon negative electrode material, carbon black and styrene-butadiene rubber in this embodiment are mixed and homogenized in a mass ratio of 85:10:5. Take a clean copper foil and clean the surface with anhydrous ethanol. After the surface is air-dried, apply the slurry on the surface of the copper foil by blade coating (silicon loading = 0.20 mg / cm 2 After drying, the electrode sheet is punched out into a negative electrode sheet with a diameter of 12 mm using a punching machine.

[0074] Example 2

[0075] A method for preparing a silicon-carbon composite material comprises the following steps:

[0076] (1) Silicon tetrachloride liquid is heated to 60° C. The resulting gas is reacted in a hydrogen atmosphere to generate silicon atoms which are deposited on a heated silicon dioxide substrate to form a two-dimensional silicon nanosheet with a thickness of 7 nm.

[0077] (2) According to the mass ratio of two-dimensional silicon nanosheets: resin: amorphous sulfur = 2:1:0.6, 112 mg of silicon nanosheets, 56 mg of resin and 33.6 mg of amorphous sulfur were weighed and added to 2 mL of DMF. A uniformly mixed slurry was obtained by ultrasonic treatment and stirring. The resin was phenolic resin.

[0078] (3) The mixed slurry was heated to 80°C to remove DMF, and then the obtained sample was carbonized at 400°C for 6 h and at 800°C in an Ar atmosphere for 3 h.

[0079] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0080] Example 3

[0081] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0082] In step (2), according to the mass ratio of two-dimensional silicon nanosheets: resin: amorphous sulfur = 2:1:0.7, 112 mg of silicon nanosheets, 56 mg of resin and 33.6 mg of amorphous sulfur are weighed and added to 2 mL of DMF, and a uniformly mixed mixed slurry is obtained by ultrasonic treatment and stirring, wherein the resin is phenolic resin.

[0083] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0084] Example 4

[0085] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0086] In step (2), according to the mass ratio of two-dimensional silicon nanosheets: resin: amorphous sulfur = 2:1:0.8, 112 mg of silicon nanosheets, 56 mg of resin and 44.8 mg of amorphous sulfur are weighed and added to 2 mL of DMF, and a uniformly mixed mixed slurry is obtained by ultrasonic treatment and stirring, wherein the resin is phenolic resin.

[0087] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0088] Example 5

[0089] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0090] In step (2), according to the mass ratio of two-dimensional silicon nanosheets: resin: amorphous sulfur = 2:0.8:0.6, 112 mg of silicon nanosheets, 44.8 mg of resin and 33.6 mg of amorphous sulfur are weighed and added to 2 mL of DMF, and a uniformly mixed mixed slurry is obtained by ultrasonic treatment and stirring, wherein the resin is phenolic resin.

[0091] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0092] Example 6

[0093] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0094] In step (2), according to the mass ratio of two-dimensional silicon nanosheets: resin: amorphous sulfur = 2:0.8:0.7, 112 mg of silicon nanosheets, 44.8 mg of resin and 39.2 mg of amorphous sulfur are weighed and added to 2 mL of DMF, and a uniformly mixed mixed slurry is obtained by ultrasonic treatment and stirring, and the resin is phenolic resin.

[0095] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0096] Example 7

[0097] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0098] In step (2), according to the mass ratio of two-dimensional silicon nanosheets: resin: amorphous sulfur = 2:0.8:0.8, 112 mg of silicon nanosheets, 44.8 mg of resin and 44.8 mg of amorphous sulfur are weighed and added to 2 mL of DMF, and a uniformly mixed mixed slurry is obtained by ultrasonic treatment and stirring, wherein the resin is a phenolic resin.

[0099] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0100] Example 8

[0101] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0102] In step (3), the obtained sample is carbonized at 350°C for 7h and at 750°C in an Ar atmosphere for 4h.

[0103] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0104] Example 9

[0105] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0106] In step (3), the obtained sample is carbonized at 450°C for 5 h and at 850°C in an Ar atmosphere for 2 h.

[0107] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0108] Example 10

[0109] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0110] The resin was replaced with an asphalt material having a softening point of 200°C.

[0111] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0112] Embodiment 11

[0113] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0114] The resin was replaced with an asphalt material having a softening point of 250°C.

[0115] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0116] Example 12

[0117] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0118] The resin was replaced with an asphalt material having a softening point of 300°C.

[0119] The method for preparing the negative electrode sheet of this embodiment is the same as that of Example 1 except that the silicon-carbon composite material of this embodiment is used.

[0120] Embodiment 13

[0121] The method for preparing the negative electrode sheet of this embodiment is different from that of Embodiment 1 in that:

[0122] The first group: using PAA to replace carbon black.

[0123] The second group: using SBR to replace carbon black.

[0124] The third group: using CMC to replace carbon black.

[0125] Comparative Example 1

[0126] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0127] Micronized silicon powder is used to replace two-dimensional silicon nanosheets.

[0128] The preparation method of the negative electrode sheet of this comparative example is the same as that of Example 1 except that the silicon-carbon composite material of this example is used.

[0129] Comparative Example 2

[0130] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0131] Silicon nanowires are used to replace two-dimensional silicon nanosheets.

[0132] The preparation method of the negative electrode sheet of this comparative example is the same as that of Example 1 except that the silicon-carbon composite material of this example is used.

[0133] Comparative Example 3

[0134] A method for preparing a silicon-carbon composite material, which differs from Example 1 in that:

[0135] In step (2), no amorphous sulfur is added.

[0136] The preparation method of the negative electrode sheet of this comparative example is the same as that of Example 1 except that the silicon-carbon composite material of this example is used.

[0137] Experimental example

[0138] The negative electrode sheets of each embodiment and comparative example are respectively prepared into batteries, comprising the following steps:

[0139] (1) Preparation of LMFP positive electrode sheet: The positive electrode powder lithium manganese iron phosphate, conductive agent carbon nanotubes, super P and binder PVDF are uniformly dispersed in the solvent NMP at a mass ratio of 90:2.5:2.5:5. The solid content of the positive electrode slurry after uniform dispersion is controlled to be 60%, and the positive electrode slurry is evenly coated on aluminum foil, dried, rolled, and die-cut for standby use. (2) Preparation of electrolyte: The mass percentage of each component in the electrolyte is: lithium hexafluorophosphate (LiPF6) 12.8%, lithium difluorooxalatoborate (LiDFOB) 1.5%, ethylene carbonate (EC) 25%, ethyl methyl carbonate (EMC) 43.2%, diethyl carbonate (DEC) 16%, vinylene carbonate (VC) 1.5%. (3) Diaphragm: A polyethylene (PE) base film 9μm plus a double-sided alumina ceramic diaphragm (Al2O3) is used. (4) Negative electrode sheet: The negative electrode sheets used are the composite silicon negative electrode sheets prepared in Examples 1 to 11 and Comparative Examples 1 to 4. (5) Preparation of battery: The positive and negative electrode sheets, separators and electrolytes are assembled into a full battery for testing.

[0140] The electrochemical performance test method of the full battery includes: standing for five minutes; 0.05C constant current discharge to 0.005V; 50 microamperes constant current discharge to 0.005V; standing for five minutes; 0.1C constant current charge to 2V.

[0141] The test results are shown in Table 1.

[0142] Table 1 Electrochemical performance test results of the battery

[0143]

[0144]

[0145]

[0146] As shown in Table 1, the silicon-carbon composite material obtained by the preparation method of the present invention, the sulfur-doped carbon framework and the silicon nanosheets cooperate to limit the volume expansion of silicon, maintain the stability of the electrode structure, and improve the cycle performance of the electrode. The first coulombic efficiency of the battery obtained by the silicon-carbon composite material of the present invention is greater than 81%, and the capacity retention rate of 250 cycles is greater than 71%.

[0147] The electrochemical performance of the silicon-carbon composite material obtained by the methods obtained in Comparative Examples 1 to 3 is relatively poor, the first coulombic efficiency of the obtained battery is relatively low, and the capacity retention rate is relatively low.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon-carbon composite material, It is characterized in that The invention comprises a silicon nanosheet and a composite carbon structure located on the surface of the silicon nanosheet, wherein the composite carbon structure comprises a carbon framework and element S, and the carbon framework and the element S form an SC bond.

2. The silicon-carbon composite material according to claim 1, It is characterized in that Contains at least one of the following features (1) to (4): (1) The composite carbon structure comprises C-SO x -C and HS x -C; (2) The ratio of the mass of the composite carbon structure to the mass of the silicon-carbon composite material is 0.7 to 0.9; (3) The mass ratio of the element S to the carbon framework is 1:(1-4); (4) The thickness of the silicon nanosheet is 5 to 10 nm.

3. The silicon-carbon composite material according to claim 1, It is characterized in that The first coulombic efficiency of the battery prepared by the silicon-carbon composite material is greater than 81%; The capacity retention rate of the battery prepared by the silicon-carbon composite material after 250 cycles is greater than 71%.

4. The method for preparing the silicon-carbon composite material according to any one of claims 1 to 3, It is characterized in that The following steps are involved: The carbon source, amorphous sulfur, silicon nanosheets and an organic solvent are mixed to obtain a mixed slurry, and the mixed slurry is heated and carbonized.

5. The method for preparing the silicon-carbon composite material according to claim 4, It is characterized in that Contains at least one of the following features (1) to (3): (1) The mass ratio of the silicon nanosheets, the carbon source and the amorphous sulfur is 2:(0.7-1):(0.6-0.8); (2) The mass ratio of the total mass of the silicon nanosheets, the carbon source and the amorphous sulfur to the organic solvent is (170-200) mg: (1.8-3) mL; (3) The carbon source comprises at least one of resin and pitch.

6. The method for preparing the silicon-carbon composite material according to claim 4, It is characterized in that Contains at least one of the following features (1) to (2): (1) The thickness of the silicon nanosheet is 5 to 10 nm; (2) The method for preparing the silicon nanosheets specifically comprises: washing the calcium disilicide with an alkaline solution and then chemically exfoliating with concentrated hydrochloric acid; Alternatively, silicon tetrachloride liquid is heat treated in a hydrogen atmosphere to obtain silicon atoms and deposit them on the surface of heated silicon dioxide.

7. The method for preparing the silicon-carbon composite material according to claim 4, It is characterized in that Contains at least one of the following features (1) to (2): (1) The mixing treatment includes ultrasonic treatment and stirring treatment; (2) The temperature of the heating treatment is 75-85°C.

8. The method for preparing the silicon-carbon composite material according to claim 4, It is characterized in that The invention comprises at least one of the following features (1) to (2); (1) The carbonization treatment includes a first carbonization and a second carbonization; the temperature of the first carbonization is 350-450° C., and the time of the first carbonization is 5-7 hours; the temperature of the second carbonization is 750-850° C., and the time of the second carbonization is 2-4 hours; (2) The carbonization treatment is carried out under protective gas conditions.

9. A negative electrode sheet, It is characterized in that A silicon-carbon composite material comprising any one of claims 1 to 3.

10. A battery, It is characterized in that A negative electrode sheet comprising the negative electrode sheet according to claim 9.

Citation Information

Cited By

  • Silicon-carbon composite material, and preparation method therefor and use thereof

    WO2026051513A1